Environmental Applications of Sorbents, High-Flux Membranes of Carbon-Based Nanomaterials - J. Suresh Babu; H. Bhavani Naga Prasanna; J. Satish Babu; Yamarthi Narasimha Rao; Surafel Mustefa Beyan (Adsorption Science & Technology)
Carbon-based nanomaterials have unique and controllable properties, making it possible to find and treat environmental challenges. There are several environmental applications for carbon-based nanoparticles: sorbents, membranes, antimicrobial agents, and sensors. According to this review, carbon-based nanomaterials have a variety of environmental benefits. This article also looks at prospective uses of nanomaterials in environmental systems, utilizing carbonaceous nanoparticles as a guide for their physical, chemical, and electrical properties.